AUDIT ASSURANCE AND MITIGATION OF FINANCIAL STATEMENTS AMBIGUITIES: AN EXPLORATORY RESEARCH - Sani Alfred Ilemona (Malete Journal of Accounting and Finance)
Financial statements of an enterprise are reports that provide information about the performance of a business useful for decision making by stakeholders. Unfortunately, the statements are often plagued with vagueness due to ambiguities. The study examined the causes of these ambiguities and explored ways they (ambiguities) could be mitigated. Relevant literature on the subject matter available from published articles available on the internet and in the library was reviewed. From the review, it was found that factors such as lack of clarity in disclosures, inconsistent application of accounting policy, use of jargon or technical terms, estimates in financial statements that require management judgment, subjectivity in valuation of items and inclusion of related party transactions to be the causes of ambiguities in financial statements. The study concluded though these ambiguities pose difficulties to users of financial statements, they can be reduced to the barest minimum. The study therefore recommended transparency in disclosure, avoidance of technical languages/terms and consistent application of accounting policy as measures that would mitigate the ambiguities capable of promoting trust and confidence of stakeholders in financial reports of enterprises.